Design, Synthesis, and Biological Activity of Novel Ferulic Amide Ac5c Derivatives - Zhang, Renfeng; Deng, Peng; Dai, Ali; Guo, Shengxin; Wang, Ya; Wei, Panpan; Wu, Jian (ACS omega, 2021)
A total of 34 novel ferulic amide Ac5c derivatives were designed and synthesized and their antipest activities were investigated. The results showed that some compounds exhibited excellent in vitro antibacterial activity against Xanthomonas oryzae pv. oryzae (Xoo) and X. oryzae pv. oryzicola (Xoc), such as compounds 4q and 5n demonstrated excellent in vitro activity against Xoo, with EC50 values of 4.0, and 1.9 μg/mL, respectively. Compounds 4c, 4h, 4m, 4p, 4q, and 5a had significant in vitro activities against Xoc, with EC50 values of 12.5, 13.9, 9.8 15.0, 9.2, and 19.8 μg/mL, respectively. Moreover, the antibacterial activity in vivo against rice bacterial leaf blight was also evaluated. Scanning electron microscopy (SEM) showed that compound 5n significantly reduced the cell membrane of Xoo, and resulted in cell surface wilting, deformation, breakage, and increased porous attributes. In addition, some of the target compounds also showed moderate biological activity against fungi and acted as potential insecticides.